2022
DOI: 10.1111/nph.18570
|View full text |Cite
|
Sign up to set email alerts
|

Root architecture plasticity in response to endoparasitic cyst nematodes is mediated by damage signaling

Abstract: Summary Plant root architecture plasticity in response to biotic stresses has not been thoroughly investigated. Infection by endoparasitic cyst nematodes induces root architectural changes that involve the formation of secondary roots at infection sites. However, the molecular mechanisms regulating secondary root formation in response to cyst nematode infection remain largely unknown. We first assessed whether secondary roots form in a nematode density‐dependent manner by challenging wild‐type Arabidopsis pl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(38 citation statements)
references
References 50 publications
2
36
0
Order By: Relevance
“…We recently reported that plant perception of cyst nematode invasion induces the formation of WOX11-adventitious lateral roots at nematode infection sites (Guarneri et al, 2023, Willig et al, 2023. Through this local root plasticity response, WOX11 compensates for the inhibition of primary root growth caused by nematode infection, which benefits overall plant growth and development (Willig et al, 2023). In this study, we shift perspective from the plant to the nematode and investigate whether WOX11-mediated developmental plasticity has an impact on nematode fecundity.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…We recently reported that plant perception of cyst nematode invasion induces the formation of WOX11-adventitious lateral roots at nematode infection sites (Guarneri et al, 2023, Willig et al, 2023. Through this local root plasticity response, WOX11 compensates for the inhibition of primary root growth caused by nematode infection, which benefits overall plant growth and development (Willig et al, 2023). In this study, we shift perspective from the plant to the nematode and investigate whether WOX11-mediated developmental plasticity has an impact on nematode fecundity.…”
Section: Discussionmentioning
confidence: 95%
“…Thus, we concluded that WOX11 does not affect plant susceptibility to nematode infection but restricts nematode female fecundity in soil. The effect of WOX11 on syncytium hypertrophy and female fecundity is not causally linked to adventitious lateral root formation WOX11-adventitious lateral roots emerge in proximity or adjacent to nematode syncytia (Golinowski et al, 1996, Willig et al, 2023. As adventitious lateral roots are both strong sinks of assimilates (Stitz et al, 2023) and an additional source of water and minerals (Levin et al, 2020), we hypothesized that they could either compete or support syncytium hypertrophy and nematode fecundity.…”
Section: Wox11 Attenuates Nematode Female Fecundity In Soilmentioning
confidence: 99%
See 2 more Smart Citations
“…Host genes related to auxin biosynthesis, distribution, and signaling are also modulated by CN at the infection site. YUCCA4 ( YUC4 ), encoding a member of YUCCA family enzymes that mediates a speed limiting step in the main auxin biosynthesis pathway, is up-regulated at the CN infection site, along with a few other auxin biosynthesis enzymes (Guarneri et al, 2022; Suzuki et al, 2022). Auxin efflux PIN1 and PIN7 genes are down-regulated at the early feeding site to prevent out flow of auxin from the initial syncytial cell, while PIN3 and PIN4 proteins are re-localized to the lateral membranes of the expanding syncytium to re-distribute auxin for lateral expansion of the syncytium (Grunewald et al, 2009).…”
Section: Introductionmentioning
confidence: 99%